Impact Analysis of Eastern Sector Red Belt Road Development in Belu Regency Border Area (Policy Study in Sisi Village and Nualain Village, Lamaknen District, Belu Regency) - Sae, Donatus; Leto Bere, Yoseph Franky (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The Eastern Sector Red Belt Road is an acceleration of infrastructure development of 3T (frontier, remote and underdeveloped) areas in the nawa cita program. The implementation of the nawa cita program in the Belu-Atambua border area is 179.99 km of state roads, 44 bridges and street lights. Approximately 5 (five) years of the construction of the Eastern Sector Red Belt Road has been completed, there are several positive opportunities for the community, especially Sisi Village and Nualain Village as users. The positive impact is one of the measures for the success of the nawa cita program for the 3T community in Sisi Village and Nualain Village, Lamaknen District, Belu Regency.